Antithrombotic Effects of DX-9065a, a Direct Factor Xa Inhibitor - Shimbo, Daichi; Osende, Julio; Chen, Julie; Robbins, Jonathan; Shimoto, Yoshimasa; Kunitada, Satoshi; Fuster, Valentin; Badimon, Juan Jose (Thrombosis and Haemostasis, 2002)
Recent evidence suggests that TF may play a causal role in acute coronary syndromes, and may be an important therapeutic target. Several inhibitors of TF, coagulation factors VIIa and Xa are under investigation as novel antithrombotic approaches. We compared the antithrombotic effects of DX-9065a, a new FXa inhibitor, vs. enoxaparin.The protocol was an open-label crossover study. Subjects (n = 6) participated in 3 consecutive study-arms: a) enoxaparin + ASA (1 mg/Kg s. c + 162 mg/day X 3 days), b) three escalating doses of DX-9065a (1 mg bolus + 0.25 mg/h X 2 h, followed by an additional 1 mg bolus + 0.625 mg/h X 2 h and, a final 1 mg bolus + 1.25 mg/h X 2 h), and c) the same doses of DX-9065a in Arm 2 plus ASA pre-treatment. The antithrombotic effects were assessed using the Badimon perfusion chamber at each dose level.The administration of DX-9065a whether alone or combined with ASA significantly inhibited thrombus formation at high and low shear rate conditions while enoxaparin did not have a significant effect. Furthermore, these antithrombotic effects were obtained without significant prolongations of the standard coagulation parameters as those induced by enoxaparin.The direct inhibition of FXa by DX-9065a appears to be a safe and effective new approach for preventing the thrombotic complications of atherosclerotic disease. The clinical effectiveness of the direct FXa inhibitors should be further investigated.
Keywords: Thrombosis; coagulation; cardiovascular diseases; plaque